2020
DOI: 10.9734/jalsi/2020/v23i830178
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Mineral Composition of the Fruit of Ficus polita

Abstract: The proximate and mineral analyses were conducted in the Department of Biochemistry Laboratory, Faculty of Basic Medical Sciences, Bayero University Kano, Nigeria, in May 2019. The study was carried out to determine the proximate and mineral composition of the fruit of Ficus polita using standard analytical methods. The fruit on dry weight basis (DW) contains moisture (9.12 %), ash (1.30 %), crude lipid (20.51 %), crude fibre (56.69 %), crude protein (1.19 %), available carbohydrates (11.40 %), and calorific v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Data in Table 1 displayed the chemical composition of raw materials used in manufacture of the functional beverages. Data presentenced are similar to Nasir et al [34] for fig fruit, and with Ragab et al, [35] for kiwi fruit, as for permeate the results is in agreement with Rizk [36].…”
Section: The Chemical Composition Of Raw Materialssupporting
confidence: 93%
“…Data in Table 1 displayed the chemical composition of raw materials used in manufacture of the functional beverages. Data presentenced are similar to Nasir et al [34] for fig fruit, and with Ragab et al, [35] for kiwi fruit, as for permeate the results is in agreement with Rizk [36].…”
Section: The Chemical Composition Of Raw Materialssupporting
confidence: 93%
“…The energetic values of food types were calculated as 37.7 kJ/g for lipids and 16.7 kJ/g for both protein and sugar (National Research Council 2003). Wendeln et al (2000) and Nasir et al (2020) found that for Ficus in Panama and Nigeria respectively, protein and lipid content of seed are significantly higher than pulp. In Ficus obtusifolia (Kunth, 1817) fruits from Panama, seeds accounted for 70.2% of the lipids, 31.3% of soluble protein, 40.6% of the nitrogen and 9.9% of the soluble carbohydrates ("sugars") contained in fruit; and similar proportions were noted for F. nymphaeifolia (Miller, 1768) (Wagner et al 2015), suggesting that the proportions can be generalized across species of this genus.…”
Section: Chemical Analysesmentioning
confidence: 99%